A Bibliometric Analysis of Sukuk using VOSviewer in Indonesia with Publish or Perish (PoP) - Lukito, Shellvy; Firmansyah, Egi Arvian (Department of Islamic Economics, IPB University, 2024)
The subject matter of sukuk has elicited increasing attention from both academic researchers and professionals within the industry. The employment of sukuk financing is effectively facilitating the progression of economic growth. The primary objective of this research endeavor is to integrate mapping analysis techniques with the utilization of VOSviewer software to conduct a comprehensive bibliometric analysis of scholarly literature pertaining to sukuk. The acquisition of research data is facilitated through the utilization of the Publish or Perish (PoP) application. The data collected has been derived from an examination of search outcomes pertaining to the keyword